Pemanfaatan Tumbuhan Sebagai Bahan Kosmetik Oleh Suku Melayu Di Kecamatan Sungai Pinyuh Kabupaten Mempawah - Mukarlina, Wahyu Styawan, Riza Linda (Universitas Tanjungpura, 2016)
Plants as cosmetic ingredients have been used by ethnic Malay in Sungai Pinyuh Subdistrict, Mempawah Regency. This research aims to find out the types of plants, forms of use and processingof plants for cosmetics by ethnic Malays in Sungai Pinyuh Subdistrict, Mempawah Regency. This research was carried out for three months from August to October 2015 in the villages of Sungai Bakau Besar Laut and Sungai Bakau Besar Darat, Sungai Pinyuh Subdistrict, Mempawah Regency. The respondents were selected using a purposive sampling technique and semi-structured interviews. The quantitative analysis was conducted to calculate the citation frequency, informant agreement ratio, percentage of plant parts, and percentage of plant habitats. Research findings showed that there are 17species and 17 families used as cosmetic ingredients. There are 5 species used for the body care; 7 species for facials, 1 species for nail care; 4 species for dental and lip care; and 3 species for hair care. Parts of the plants widely used as ingredients in cosmetics are the leaves (57.93%). The highest citationfrequency in this research reaches 54.16% i.e. the henna plant (Lawsonia inermis L). The methods of processing the plants for cosmetics are by heating, kneading, crushing or mixing with other ingredients. The use as cosmetics for nail care receives the highest informant agreement ratio (IAR) i.e. 1, while the lowest informant agreement ratio is 0.857.